(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Study Is A Part Of The Impacts Research In The Sociology Of Communication It Aims To Know The Youth Visions Of The Network Community As Well As The Services And The Needs That It Satisfies To Know How Users Choose Their Identity. On One Hand. And The Effect On Their Virtual Identities On The Other Hand. The Study Seeks To Try To Understand The Relationship Between True Identity And Virtual One. Also To See If It Takes The Form Of A Connection Or A Breakup. Key Words: The Network Society , Virtual Identity , Social Media, Young.